Dried Blood Spot Tests for the Diagnosis and Therapeutic Monitoring of HIV and Viral Hepatitis B and C - Tuaillon, Edouard; Kania, Dramane; Pisoni, Amandine; Bollore, Karine; Taieb, Fabien; Ontsira Ngoyi, Esther Nina; Schaub, Roxane; Plantier, Jean-Christophe; Makinson, Alain; Van de Perre, Philippe (Frontiers in Microbiology, 2020)
Blood collected and dried on a paper card - dried blood spot (DBS) - knows a growing interest as a sampling method that can be performed outside care facilities by capillary puncture, and transported in a simple and safe manner by mail. The benefits of this method for blood collection and transport has recently led the World Health Organization to recommend DBS for HIV and hepatitis B and C diagnosis. The clinical utility of DBS sampling to improve diagnostics and care of HIV and hepatitis B and C infection in hard to reach populations, key populations and people living in low-income settings was highlighted. Literature about usefulness of DBS specimens in the therapeutic cascade of care - screening, confirmation, quantification of nucleic acids, and resistance genotyping - , was reviewed. DBS samples are suitable for testing antibodies, antigens, or nucleic acids using most laboratory methods. Good sensibility and specificity have been reported for infant HIV diagnosis and diagnosis of hepatitis B and C. The performance of HIV RNA testing on DBS to identified virological failure on antiretroviral therapy is also high but not optimal because of the dilution of dried blood in the elution buffer, reducing the analytical sensitivity, and because of the contamination by intracellular HIV DNA. Standardised protocols are needed for inter-laboratory comparisons, and manufacturers should pursue regulatory approval for in vitro diagnostics using DBS specimens. Despite these limitations, DBS sampling is a clinically relevant tool to improve access to infectious disease diagnosis worldwide.